(untitled) (American Journal of Technology and Applied Sciences, 2022)
Prospects for the technical improvement of sheet stamping, both in terms of increasing the productivity of pressing equipment and in terms of creating new high-performance processes, provide for a significant increase in production and widespread introduction of adjustable dies.